A study on the characteristics of cognitive function in patients with multiple system atrophy in China - Li, Nannan (Sci Rep, 2021)
Nonmotor symptoms in patients with multiple system atrophy (MSA) have received an increasing amount of attention in recent years, but no research on MSA patients' cognitive characteristics has been conducted in China. To evaluate the cognitive function of MSA patients in China. Using a case–control study design, 256 MSA patients and 64 controls were evaluated by the Montreal cognitive assessment (MoCA) scale to characterize their cognitive function. Like the controls, 60.5% of the patients with MSA had cognitive impairment, but the characteristics of cognitive impairment between the two groups were different. The cognitive impairment in MSA patients was prominent in the cognitive domains of visuospatial/executive functions, naming, attention, and orientation; particularly, the visuospatial/executive functions were the most significantly impaired, while impairment in language function was mainly seen in the controls. Besides, impairments in visuospatial/executive functions, attention, language, and orientation were more prominent in MSA-P (MSA with predominant Parkinsonism) patients than in MSA-C (MSA with predominant cerebellar ataxia). The cognitive impairments were more severe in patients with probable MSA than in patients with possible MSA. In addition, the results showed that the level of cognitive function was negatively correlated with the severity of MSA. This study, which characterized the cognitive function of MSA patients with the largest sample size known so far in China, found that patients with MSA do have cognitive impairment and display specific characteristics. Therefore, the cognitive impairment of MSA should be paid more attention. The study has been registered in the Chinese Clinical Trial Registry (ChiCTR) (Registration No: ChiCTR1900022462).